2001
DOI: 10.1074/jbc.m107080200
|View full text |Cite
|
Sign up to set email alerts
|

The Sorting Nexin, DSH3PX1, Connects the Axonal Guidance Receptor, Dscam, to the Actin Cytoskeleton

Abstract: Dock, an adaptor protein that functions in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
81
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 52 publications
3
81
0
Order By: Relevance
“…This spatial and temporal heterogeneity, which has also been observed for actin's association with CCPs (Yarar et al, 2005), may reflect a dual role for SNX9 in endocytosis. In this regard, it is interesting that SNX9 has been shown to interact with WASP in Drosophila (Worby et al, 2001). We did not detect gross differences in phalloidin staining of the actin cytoskeleton in control versus SNX9 siRNA-treated cells (unpublished data).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…This spatial and temporal heterogeneity, which has also been observed for actin's association with CCPs (Yarar et al, 2005), may reflect a dual role for SNX9 in endocytosis. In this regard, it is interesting that SNX9 has been shown to interact with WASP in Drosophila (Worby et al, 2001). We did not detect gross differences in phalloidin staining of the actin cytoskeleton in control versus SNX9 siRNA-treated cells (unpublished data).…”
Section: Discussionmentioning
confidence: 85%
“…Both have SH3 domains and BAR domains, and both proteins bind dynamin, AP2, clathrin, and lipids. Finally, both have been implicated in regulation of the actin cytoskeleton (Mundigl et al, 1998;Worby et al, 2001). Thus, it has been suggested that SNX9, like amphiphysin, might function as an endocytic scaffold to recruit dynamin to the plasma membrane as CCPs assemble (Lundmark and Carlsson, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Drosophila does not have DNA rearrangements that occur during immune cell development in humans. However, the Drosophila immune system utilizes alternative splicing of the Ig-domain protein DSCAM which has over 18,000 alternative-splice isoforms (Schmucker et al, 2000;Schmucker and Flanagan, 2004;Watson et al, 2005;Worby et al, 2001). All in all, there are likely well over 100,000 protein products in both humans and Drosophila, but the precise numbers are not yet known.…”
Section: Microarrays and Nutrition Studies In Microarrays And Nutritimentioning
confidence: 99%